Human reproductive and prenatal genetics - Leung, P. C. K; Qiao, Jie (Academic Press, an imprint of Elsevier, 2019)
Human Reproductive and Prenatal Genetics covers the field of human reproductive and prenatal genetics and presents the latest material from a detailed molecular, cellular and translational perspective. This book aims to be among the largest and most useful references available. Considering its timeliness and potential international impact, this all-inclusive and authoritative work is ideal for researchers, students, and clinicians worldwide.
Keywords: preimplantační diagnóza; Preimplantation Diagnosis; reprodukční lékařství; asistovaná reprodukce; gametogeneze; Reproductive Techniques, Assisted; pohlavní orgány; molekulární biologie, molekulární medicína; Genitalia; Infertility; Gametogenesis; infertilita; embryologie a teratologie